Le invenzioni tecnologiche di Michele Sambin nello spazio teatrale - D’Amico, Flavia Dalila (Mimesis Journal, 2021)
The paper focuses on the technological inventions made by the artist Michele Sambin during his activity with the Tam Teatromusica theater group, founded in 1980 together with Pierangela Allegro and Laurent Dupont. Since 1970s Michele Sambin has been conducting a research across multiple artistic territories – painting, music, cinema, video, performance and theater –, recombining their codes in the idea of probing the possibilities of relationship and conflict between images and sounds. This peculiar interdisciplinary approach is combined with the constant interest in subverting and reinventing the technological tools available on the marketplace. While taking into account the historical-critical contexts and the linguistic and aesthetic changes that have marked the various decades of the Italian and international theatrical practices from the 1980s till today, the analysis attempts to restore the richness of the artist’s experiments, assuming as lines guides the technical and technological inventions that from time to time have forged the conceptual and aesthetic dimensions of Tam Teatromusica’s performances. However, reading the history of this group through the lens of the technological devices used, does not mean considering its artistic production as a deterministic response to technological innovation, it means shifting the emphasis on the interrelation between the technical and expressive possibilities of the tools, the discourses that orient their uses and practices that reinterpret their values, discarding their underlying ideologies.